(3GdbGfhf GdEOGQj (B/s - (3bhOjd, LhQLs; (3Odbhdbjg, HjGQs ((3HjQhJ(B: s (3GdeDSSI GdLGeYjI ddOQGSGJ hGdfTQ hGdJhRjY(B, s, 2001)
(3GdbGVj GdEOGQj(B- (3eHGOF YGeI(B- (3JfXje GdCLgRI GdbVGFjI GdEOGQjI(B- (3JhRjY GdUdGMjGJ Hjf GdCLgRI GdbVGFjI GdEOGQjI(B- (3GdELQGe CeGe GdGLgRI GdbVGFjI GdEOGQjI(B- (3GdeQGLYI dJLGhR MO GdSdWI(B- (3JfajP bQGQGJ GdbVGA VO GdEOGQI(B- (3GdeYWjGJ GdbGfhfjI hGdJbfjI hGdJGQjNjI dJfXje GdEOGQI(B- (3EOGQI GdOhdI(B- (3GdLeGYGJ GdeMdjI(B- (3GdeDSSGJ GdYGeI(B- (3eaGgje YGeI Mhd GdYed GdEOGQj(B- (3GdeQab GdYGe(B.s
(3GdLRA (B2 (3GdeLdO GdKGdKs
Keywords: (3GdEOGQIs; (3GdbGfhf GdEOGQjs